2019
DOI: 10.1093/inthealth/ihz071
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of chronic kidney disease in Peru and its relation to social determinants of health

Abstract: Background Chronic kidney disease (CKD) is a growing public health problem and an important cause of morbidity and mortality. Disparities in CKD may be related to social determinants and health inequalities in low- and middle-income countries. This study determined how social determinants of health influence trends in the prevalence and mortality of CKD in Peru. Methods This was an ecological study based on a secondary analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…CKD has emerged as a public health concern in Peru due to its increasing mortality and lack of early detection. A study using healthcare and death records from the Peruvian Ministry of Health evidenced an increase of 300% of CKD prevalence between 2010 and 2016, especially in the Tumbes region [ 34 ]. In addition, another study reported that the proportionate mortality due to CKD has also increased in this region during the last 15 years [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…CKD has emerged as a public health concern in Peru due to its increasing mortality and lack of early detection. A study using healthcare and death records from the Peruvian Ministry of Health evidenced an increase of 300% of CKD prevalence between 2010 and 2016, especially in the Tumbes region [ 34 ]. In addition, another study reported that the proportionate mortality due to CKD has also increased in this region during the last 15 years [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Public health relevance CKD has emerged as a public health concern in Peru due to its increasing mortality and lack of early detection. A study using healthcare and death records from the Peruvian Ministry of Health evidenced an increase of 300% of CKD prevalence between 2010 and 2016, especially in the Tumbes region [34]. In addition, another study reported that the proportionate mortality due to CKD has also increased in this region during the last 15 years [19].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…CKD has emerged as a public health concern in Peru due to its increasing mortality and lack of early detection. A study using healthcare and death records from the Peruvian Ministry of Health evidenced an increase of 300% of CKD prevalence between 2010 and 2016, especially in the Tumbes region [36]. In addition, another study reported that the proportionate mortality due to CKD has also increased in this region during the last 15 years [19].…”
Section: Public Health Relevancementioning
confidence: 99%